The Relevance of Academic Work in Comparative Perspective
X, 252 p. 34 illus., 18 illus. in color.
Keywords: This book is the first of two volumes that look at the changed landscape of higher education and the academic profession. This volume focuses on academic work, examining the significant changes that have taken place in the backgrounds, specialisations, expectations and work roles of academic staff. The academic profession is ageing, and becoming increasingly insecure, more accountable, more internationalised and less likely to be organised along disciplinary lines. The private sector is more prominent, expectations from society are different and increasing, professional roles are evolving, and there is a new devotion to knowledge. This leads to questions about the attractiveness of an academic career and the quest for greater relevance of research. This book discusses in detail the themes that are common in this changed arena, such as the context for change, the relation of teaching to research, research productivity, applied and commercial research, and the relevance of teaching and research.